Constraints Perceived By The Dairy Farmers In Adoption Of Scientific Dairy Farming Practices In Sikar District - Khyalia, N.K.; Sagar, M.P.; Chander, Mahesh; Pratap , J. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
The present study was carried out to find the constraints perceived by the dairy farmers in adoption of scientific dairy farming practices in the Sikar district of Rajasthan in the 4 randomly selected villages of two blocks with a total sample size of 120 households. The results revealed that major constraints faced by dairy farmers in breeding, feeding, management and health-care practices were inadequate knowledge of breeding practices (71.67%), high cost of cattle feed like concentrate and roughage (88.33%), lack of interest in maintaining simple records (81.67%) and high cost of treatment/veterinary medicines (87.50%).
Keywords: Constraints; Dairy farming; Adoption; Health care; Breeding; Feeding